1985
DOI: 10.1007/bf01258453
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regeneration from GABAergic neurons in the adult rat thalamus

Abstract: Peripheral nerve grafts were inserted into the thalamus in 27 Sprague-Dawley rats. From 6 weeks to 15 months later, horseradish peroxidase (HRP) was applied to the extracranial end of each graft and sections of the brains reacted for peroxidase histochemistry. Of the thalamic neurons that were retrogradely labelled with HRP, more than 80% were located in the reticular nucleus of the thalamus (RNT), a distinct group of nerve cells that contain glutamic acid decarboxylase (GAD)-like immunoreactivity and are pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 36 publications
4
25
1
Order By: Relevance
“…We have shown that the axons regenerating into tibial nerve autografts placed in the dorsal thalamus originate predominantly from neurons in the TRN, confirming previous observations (Benfey et al, 1985;Morrow et al, 1993) and attesting to the strong regenerative propensity of this nucleus. The TRN forms a sheet of variable thickness partially enveloping the dorsal thalamus, with axons that project to dorsal thalamic nuclei, where they regulate the thalamocortical output (e.g., Ohara et al, 1983;Jones, 1985).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We have shown that the axons regenerating into tibial nerve autografts placed in the dorsal thalamus originate predominantly from neurons in the TRN, confirming previous observations (Benfey et al, 1985;Morrow et al, 1993) and attesting to the strong regenerative propensity of this nucleus. The TRN forms a sheet of variable thickness partially enveloping the dorsal thalamus, with axons that project to dorsal thalamic nuclei, where they regulate the thalamocortical output (e.g., Ohara et al, 1983;Jones, 1985).…”
Section: Discussionsupporting
confidence: 84%
“…Neurons in the central nervous system (CNS) of adult mammals cannot normally regenerate their axons following injury, but it is now well established that axotomised CNS neurons can regenerate axons for long distances through segments of peripheral nerve implanted into the brain or spinal cord or attached to the retinal stump of severed optic nerves (David and Aguayo, 1981;Benfey et al, 1985;Aguayo, 1985;Berry et al, 1986). Not all populations of CNS neurons show the same propensity for axonal regeneration.…”
Section: Indexing Terms: Axotomy; Cns Regeneration; Nerve Graft; Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…These ob servations confirm and extend recent findings of axonal re generation into peripheral nerve grafts [1][2][3][4][5][6]9. II.…”
Section: Discussionsupporting
confidence: 80%
“…Neurons in the cerebellar cortex of adult rats do not regenerate their axons into peripheral nerve grafts placed into the subcortical white matter of the cerebellum, whereas neurons in the deep cerebellar nuclei may do so (Dooley and Aguayo, 1982;Vaudano et al, 1993). The best documented example of differential regenerative responses is provided by studies involving the insertion of peripheral nerve grafts into the thalamus: in most experiments, more than 90% of the neurons that regenerate axons into such grafts have cell bodies in one nucleus, the thalamic reticular nucleus (TRN); by comparison, only a few thalamic projection neurons, always with cell bodies situated close to the graft tip, regenerate axons into the same grafts (Benfey et al, 1985;Morrow et al, 1993). Neurons of the TRN regenerating their axons into peripheral nerve grafts markedly upregulate their expression of mRNAs for the growth-associated protein 43 (GAP-43; Vaudano et al, 1995), which is involved in axonal growth and/or pathfinding (Skene, 1989;; the cell recognition molecule L1 (Zhang et al, 1995), which is known to be involved in axonal elongation during development and regeneration (Schachner, 1994); and the immediate early gene c-jun (Vaudano et al, 1993), a transcription factor, elevated expression of which precedes and accompanies axonal regeneration in the peripheral nervous system (e.g., Jenkins et al, 1993).…”
mentioning
confidence: 99%